Healing Potential of Nature: An Analysis of Gopinath Mohanty’s LayaBilaya:High Tide, Ebb Tide - Gill, Navdeep Kaur (International Journal of Psychosocial Rehabilitation, 2020)
The present paper intends to explore the healing power of nature in Gopinath Mohanty’s LayaBilaya: High Tide, Ebb Tide. Mohanty has a very profound love for nature that reflects in all his works. Co- existence with nature is the fundamental need of humanity that not only provides physical but also emotional well-being, bringing positivity, high-spiritedness andalleviating feelings of loneliness or emptiness. It becomes a medium to establish bonds with the Supreme force paving way for spiritual awakening.